Applying small group discussion to improve the ability to convey opinions orally on recount text material - Gaffar, Muhammad Andriana; Gumelar, Wahyu Satya; Hasanah, Huswatun; Fadilah, Laila Putri (Universitas Islam Sultan Agung, 2024)
The ability to use a language to convey ideas, feelings and thoughts orally is called speaking. This shows that speaking skills are crucial to learn, including for students at school. In this way, teachers are expected to be more innovative in finding learning methods or models that can improve students’ speaking skills. The small group discussion learning model is considered to be the right treatment because it can increase students’ confidence in speaking, increase interaction between students, and students become more active in contributing to learning. The aim of carrying out this research is to find out how the application of the Small Group Discussion learning model to students affects their speaking skills, especially in conveying opinions orally in English. This research used a quantitative approach with experimental research method. This research was carried out at MA Plus Darul Hufadz Jatinangor. Participants in this research were students from classes X-A and X-B, each class consisting of 20 students. Data was collected using tests in the form of presentations from students. The results show that implementing the Small Group Discussion can have a significant influence on students’ ability to convey opinions orally using English. This is proven by the average (mean) score of the experimental class learning results reaching 74,20, while the mean score of the control class only reached 65,00. It can be concluded, that the Small Group Discussion can have a positive impact on the learning process and student learning outcomes, especially in language skills. By implementing Small Group Discussion, students are seen interacting with each other more often, they show a positive response to the application of this learning model in their learning activities.